Crime prevention through environmental design - Crowe, Timothy D (Butterworth-Heinemann is an imprint of Elsevier, 2013)
Crime Prevention Through Environmental Design, Second Edition is a vital book for anyone involved in architectural design, space management, and urban planning. The concepts presented in this book explain the link between design and human behavior. Understanding this link can enable a planner to use natural environmental factors to minimize loss and crime and to maximize productivity. This practical guide addresses several environmental settings, including major event facilities, small retail establishments, downtown streets, residential areas, and playgrounds. A one-stop resource with explanations of criminal behavior and the historical aspects of design, it teaches both the novice and the expert in crime prevention how to use the environment to affect human behavior in a positive manner. Fully updated with substantial new material in each chapter Useful illustrations describe the design and layout concepts in an easy to understand manner Written by a well-qualified author in the field of crime prevention